Synthesis of Au-Cu/SBA(Ti) catalysts for photocatalytic applications - Barroso-Martín, Isabel (My University, 2018)
In this work, it has been synthesized several Au and Au-Cu alloy photocatalysts supported on two different mesoporous supports: a non-commercial SBA-15 and a post-synthesis TiO2 modified SBA-15 (TiSBA-15), with which a high dispersion of TiO2 species have been achieved maintaining the SBA-15 structure. In addition, it has also been obtained highly dispersed Au nanoparticles confined in SBA-15 pore channels. The photocatalysts have been preliminary tested in the preferential CO oxidation in a H2-rich stream (CO-PROX) at room temperature and atmospheric pressure under simulated solar light irradiation. In spite of the very low gold and copper loading (1.5 wt% and 0.5wt% respectively), the catalysts resulted active and selective in the low temperature photo-CO-PROX.
Keywords: Fotocatálisis; Photocatalysis; Gold; Copper; Mesoporous silica; CO-PROX; Titania